The concealed interment of a first‐trimester foetus in Gällared Parish Church (1831), Sweden: Age estimation and reconstructed taphonomy. (7th February 2021) - Maltin, Emma; Turner‐Walker, Gordon; Tegnhed, Stina; Peacock, Elizabeth E.
Abstract: In 2015, during architectural restoration works on the parish church (1831) in Gällared, Sweden, a small wooden box was discovered beneath the floorboards. Unaware of the possible significance of the box and its contents, workers on site removed its lid, revealing a piece of folded cloth. This was later found to be wrapped around fragments of human foetal remains. Although largely forgotten now, concealed interment of foetuses in, and around, churches was formally a well‐known custom in Nordic Europe. Osteological and archaeological examinations of these are rare because the containers are recognised as a form of mortuary ritual and are thus neither removed from the church nor investigated for obvious ethical reasons. The occasion of this providentially found concealed interment provided an opportunity to undertake a systematic study of the coffin and its contents prior to it being reinterred. This paper focuses on the foetal remains: their identification, assessment of age at death and the taphonomic circumstances leading to their preservation, as well as the broader insights this funerary behaviour sheds on the meanings of personhood, infant death and grief. Visual and microscopic analyses conclude that the foetus was miscarried in its first trimester, in Week 9, making it possibly one of the youngest ever reported to be recovered from an archaeological context. Examination of the skeletal elements highlights both the difficulty in ageing early‐stage archaeological foetal skeletons and the paucity of comparative foetal bone size material. The onset of ossification and the development of the mandible as ageing indicators show significant potential. Detailed examination of the wooden coffin, cotton burial shroud and insect fauna, together with an understanding of foetal body chemistry and the circumstances of interment, support the hypothesis that the bones' survival was facilitated by a process of natural mummification prior to becoming fully skeletonised by insects.